1961
DOI: 10.1083/jcb.11.1.207
|View full text |Cite
|
Sign up to set email alerts
|

The Structure of the Yolk of the Hen's Egg as Studied by Electron Microscopy

Abstract: A description of the fine structure of the yolk of the unincubated hen's egg has becn providcd, which will serve as a basis for further studies on yolk digestion. The gross components of the yolk (that is, free-floating lipid drops, ycllow and white yolk spheres together with their enclosed lipid subdroplcts, and aqueous protein fluid) could be recognized by phasc contrast and low power electron microscopy. The majority of the lipid drops, whether free floating or enclosed within yolk spheres, were composed of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
67
1

Year Published

1970
1970
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(73 citation statements)
references
References 12 publications
5
67
1
Order By: Relevance
“…This material (Fig. 2), identified as coming from the latebra, always had the typical structure of white yolk as reported by Riddle (1911), Romanoff and Romanoff (1949), and Bellairs (1961). Samples from the rest of the yolk were always typical of yellow yolk (Fig.…”
Section: Resultsmentioning
confidence: 55%
See 2 more Smart Citations
“…This material (Fig. 2), identified as coming from the latebra, always had the typical structure of white yolk as reported by Riddle (1911), Romanoff and Romanoff (1949), and Bellairs (1961). Samples from the rest of the yolk were always typical of yellow yolk (Fig.…”
Section: Resultsmentioning
confidence: 55%
“…2 and 3), have long been known to occur in the hen's egg. It has generally been accepted that the yolk is made up of concentric and alternate layers of yellow and white yolk laid down around the elongated latebra (see Riddle 1911;Romanoff and Romanoff 1949;and Bellairs 1961); that the latebra, opening into the nucleus of Pander beneath the blastodisc of the unfertilized egg, also contains white yolk; and that the layers of white yolk are deposited during An optical micrograph of part of a specimen grid has been superimposed on an optical micrograph of yellow yolk (same magnification) to indicate the difficulties associated with the electron microscopy of this material. The small amount of material which can be photographed on a plate (6·5 X 9·0 em) in the microscope at a magnification of X 5,000 is judged if the present magnification is increased 12·5 times.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Abraham et al (1960) isolated the lowdensity lipoproteins from both egg yolk and hen serum and found they contained galactose, mannose, glucosamine, and sialic acid as the only carbohydrate constituents.. Using electron microscopy Bellairs (1961) found the lipid drops and the yolk sphere subdroplets to be about 2n in diameter and to contain, in turn, small dense particles from 30 to 60 in diameter. She found the continuous phase of yolk to contain small spherical particles about 250 A° in diameter.…”
Section: Lipidsmentioning
confidence: 99%
“…Burley and Cook (1961), as previously mentioned, isolated yolk granules (as described by Romanoff and Romanoff,19^9) and found that they contained the lipovitellins, phosvitin, and a smaller amount of low-density lipoprotein. Wallace (1963) reports that Colvin and Cook believe these granules to be the lipid drops and yolk sphere subdroplets of Bellairs (1961). However, since Bellairs (1961) apparently found the yolk sphere subdrop lets to be similar to the free-floating lipid drops, and since Burley and Cook (1961) reported their sedimented granules were free of contaminating yolk spheres (which they called globules), there appears to be some confusion as to which proteins or lipoproteins are found in each of the various microscopic structures.…”
Section: Lipidsmentioning
confidence: 99%